Genomic and Bioinformatic Characterization of Mouse Mast Cells (P815) Upon Different Influenza A Virus (H1N1, H5N1, and H7N2) Infections - Huo, Caiyun; Wu, Hongping; Xiao, Jin; Meng, Di; Zou, Shumei; Wang, Ming; Qi, Peng; Tian, Haiyan; Hu, Yanxin (Frontiers in Genetics, 2019)
Influenza A virus (IAV) is one of the segmented negative-stranded RNA virus, which brings a potentially serious threat to public health and animal husbandry. Mast cells, a kind of immune cells, play an important role in both inherent and adaptive immune response. Previous studies indicated that mast cells support the productive replication of H1N1, H5N1 and H7N2. To date, the distinct of molecular mechanism behind the pathogenesis in mast cells among three different viruses was poorly understood. In the present study, we investigated the more profound genomic profiles for the first time and describe the dynamic change of genomes regulated by different subtypes of IAV in mouse mast cells using microassays. Compared with any two of the three IAV-infected groups, much more diﬀerentially expressed genes (DEGs), cellular functions and signaling pathways were confirmd in H1N1 or H7N2 group, and H7N2 group showed the highest levels. However, few DEGs were detected as well as various cellular functions and signaling pathways were dramatically suppressed in H5N1 group. With an in-depth study on H1N1 and H7N2 group, we demonstrated the essential role of 5-HT signaling pathway and cGMP/PKG signaling pathway that were preferentially activated in P815 cells infected by H1N1 while crucial role of HIF-1 signaling pathway that were preferentially activated in P815 cells infected by H7N2 virus. Furthermore, RT-qPCR results also showed significantly increased mRNA of 5-HT and PKG in H1N1-infected P815 cells as well as HIF-1 in H7N2-infected P815 cells. Besides, exosomes were also preferentially secreted from H1N1-infected or H7N2-infected P815 cells that are potentially pivotal in innate immunity to fight IAV infection. The study provides novel information and insight into the distinct of molecular mechanism of H1N1, H5N1 and H7N2 viruses in mast cells from the perspective of genomic profiles.